Trust, Network Capital, and Informality – Cross-Border Entrepreneurship in the First Two Decades of Post-Communism - Sik, Endre (Szociológiai Szemle, 2023)
The paper addresses two of the manifold forms of transformation-specific cross-border entrepreneurial activities and shows the role of particularistic trust and network capital as embedded in these processes. The two case studies illustrate that these activities are “borderline” cases in three senses: (a) using national borders as an opportunity structure, (b) using ethnicity as a resource to gain trust, and as a defensive mechanism, and (c) creating a semi-permeable zone between the formal and informal economy. The first one is about old/new form of urban informal trade: the combination of crossborder trade, street vending, and COMECON-marketplace in Mongolian cities in 2000. The second case study is about inter-regional form of informal trade, i.e. the so-called cross-border junk trade, which is a particularly “high-trust” and network capital-intensive form of cross-border entrepreneurship.